2019
DOI: 10.1111/jvh.13100
|View full text |Cite
|
Sign up to set email alerts
|

Serum keratin‐18 fragments as cell death biomarker in association with disease progression and prognosis in hepatitis B virus‐related cirrhosis

Abstract: Extensive hepatocyte death leads to hepatic inflammation and contributes to systemic inflammation in decompensated cirrhosis. We aimed to investigate the prognostic value of serum cell death markers in patients with hepatitis B virus (HBV)‐related acute decompensation (AD) of cirrhosis with and without acute‐on‐chronic liver failure (ACLF). We studied two cohorts—cohort 1: 201 outpatients with stable chronic hepatitis B (49 cirrhosis); cohort 2: 232 inpatients with HBV‐related cirrhosis admitted for AD. Cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…We have recently provided evidence that the high level of cell death in HBV decompensated cirrhosis patients is mostly due the flare‐up of hepatitis B and leads to poor short‐term outcome . Recognizing that the presence of HBV flare could have potential negative impacts on patients with decompensated HBV cirrhosis, it is imperative that every effort should be made to assess patients with HBV, and provide access to anti‐HBV treatment as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently provided evidence that the high level of cell death in HBV decompensated cirrhosis patients is mostly due the flare‐up of hepatitis B and leads to poor short‐term outcome . Recognizing that the presence of HBV flare could have potential negative impacts on patients with decompensated HBV cirrhosis, it is imperative that every effort should be made to assess patients with HBV, and provide access to anti‐HBV treatment as appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death mechanisms including apoptotic pathways influence the recovery of HBV-related ACLF ( 28 ). Recently, it has been identified that caspase-cleaved keratin-18 (ck18) can predict the progression of acute decompensation to ACLF ( 29 ). Biomarkers including caspase-cleaved neoepitope of cytokeratin-18 and intact cytokeratin-18 variant recognized as M30 and M65, respectively have been investigated in ACLF.…”
Section: Pathophysiological Mechanisms In Aclfmentioning
confidence: 99%
“…It has been reported that cell death in large numbers is a core event in the progression of liver diseases (Malhi et al, 2010;Cao et al, 2016). Development of CHB is mainly due to persistent hepatic inflammation and hepatocyte death, including apoptosis and necrosis, which ultimately leads to liver failure (Luedde et al, 2014;Cao et al, 2015Cao et al, , 2019a. More recently a caspase-independent mode of programmed cell death, termed necroptosis, has been shown to be similar to apoptosis because of the tight regulation by distinct molecules, but it is also characterized by morphological features of necrosis (Declercq et al, 2009;He et al, 2009;Christofferson and Yuan, 2010).…”
Section: Introductionmentioning
confidence: 99%